ROLA REFLEKSJI W NAUCZANIU DOROSŁYCH SŁUCHACZY KOMERCYJNYCH KURSÓW JĘZYKOWYCH - Pudo, Dorota (Neofilolog, 2019)
This article examines various levels of reflection in language learning and teaching, such as reflecting on one’s own foreign language production, on the language system in general, on one’s learning habits and, in the case of the teacher, on the teaching process. The author hypothesizes that all of these are bound to change some of their characteristics depending on features such as age of the learner and learning context. The article examines reflection in adult students of commercial language courses, trying to point out that all the levels of reflection mentioned are supposed to increase in this group. Age is proved to increase language-focused reflectivity in the subjects, whereas the specific learning context might, for reasons of strong personal motivation, be an asset in encouraging learner reflections on their own learning strategies. These conclusions are nonetheless to be treated with caution, for some specific inhibitors to reflection might appear in this group as well, and further research is needed to confirm this possibility.